O19.5 Assessing the Effectiveness of the Human Papillomavirus (HPV) Vaccination Programme in Victoria, Australia. (13th July 2013) - Garland, S M; Osborne, S O; Young, E J; Brotherton, J M L; Tabrizi, S N; Gertig, D M; Jayasinghe, Y
Abstract : Background: Quadrivalent HPV vaccination has been available in Australia through the National HPV Vaccination Program since 2007. The VACCINE study aims to evaluate the effectiveness of the programme by assessing the prevalence of vaccine targeted HPV genotypes (HPV 6, 11, 16 and 18). We aim to detect any decrease in prevalence of vaccine-targeted HPV genotypes amongst young women in vaccine eligible cohorts and to independently measure vaccine coverage in young Victorian women. Methods: Young Victorian women aged 18–25 are recruited using the social networking site Facebook. Participants complete an online questionnaire and those sexually active are asked to provide a self-collected vaginal swab. Swabs are genotyped using a Linear Array HPV genotyping test (Roche Diagnostics). Results: To date, 623 (of 1570) females have been recruited into the study and 477 participants have completed the study. 71% (440) were sexually active and of these women 373/440 (85%) provided a self-collected swab, of which 75% were negative for HPV. Of the 95 cases positive for HPV, only 6 cases of HPV 16 have been recorded, and no cases of HPV 6, 11 or 18 have been identified. The prevalence of HPV16 (1.6%) is significantly lower than that detected from pre-vaccine age matched Victorian women cervical specimens (9.4%) (χ 2 (1) = 18.3, p < 0.001). Based on self-reported vaccination status, 85% of women aged 18–21 years old in our sample have received at least one dose of the HPV vaccine, compared with 83% for women aged 22–25. Cross protection against HPV 31 is also being seen (0.5% versus 5.6%, χ 2 (1) = 14.2, p < 0.001). Conclusions: Preliminary data from the VACCINE study suggest a significant decline in the prevalence of vaccine-targeted HPV genotypes. These results support the hypothesis that the HPV vaccine programme is effective in reducing HPV genotypes 6, 11, 16 and 18 amongst populations offered the vaccine.